From professional aspirations to identity confirmation and transformation: The case of Japanese career women working for foreign subsidiaries in Japan - Markus Pudelko; Helene Tenzer (Human Resource Management Journal, 2023)
This study investigates what attracts career-oriented women to foreign subsidiaries and how they experience this work context. Based on 125 interviews with career-oriented women in Japan, we find that their frequent choice of foreign employers is not only motivated by professional aspirations but also by identity-related aspirations . Japanese women who embraced an internationalist orientation experience a confirmation of their identity by working for foreign subsidiaries; by contrast, those who still felt bound by traditional role expectations, undergo a liberating identity transformation . Based on the perceptions of these particular employees, we develop recommendations for gender diversity management in foreign subsidiaries. We further argue that women, who are disadvantaged in the local employment context, often desire that foreign subsidiaries implement standardized home country human resource management practices , instead of adopting local practices. By focusing on the recruitment of highly qualified women, foreign subsidiaries may turn their liability of foreignness into a competitive advantage.
Keywords: 650; career; diversity management; foreign subsidiaries; gender equality; identity; international human resource management; Japan